NATIONAL COSTUMES IN THE EPIC “THE BOOK OF DEDE GORGUD” - Almara Vazir gizi Nabiyeva (International Journal of Innovative Technologies in Social Science, 2025)
In the article the information about the history of the creation of the national costumes, which is found in the epic “The Book of Dede Gorgud” is given. From the study, it becomes clear that the national costumes in the epic were created by the Oghuz Turks, improved over thousands of years and from here they spread throughout the world. One of the most valuable information given in the epic is the idea that has come down to us about the types of clothing. The various dresses of the heroes and ladies at ceremonies, jewelry and jewels remain relevant. One of the main features of the epic “The Book of Dede Gorgud” is Dede’s giving clothes along with the name to the heroes for the courage shown by them. According to the disclosing the ethnographic richness the epic is a fundamental resource.